Class Consciousness and Class Conflict in Capture Fishery in Indonesia - Kinseng, Rilus A (Journal of Rural Indonesia, 2013)
This paper discusses about class structure, and then followed by discussion on class consciousness and class conflict in capture fisheries in Indonesia, taking fishers in Balikpapan, East Kalimantan as the case.  Data were collected from January to September 2006 intermittently, mainly through interviews with fishers, government officials, and NGO activists. This research is a qualitative research. In terms of class structure, there are four classes of fishers found in Balikpapan, East Kalimantan, namely: labour fishers, small scale fishers, intermediate or medium fishers, and large scale or capitalist fishers.  It is argued that class consciousness of the labour fishers has not developed yet. Therefore, labour fisher is only a class in itself, not as a class for itself. There are six factors that contribute to the underdeveloped of the class consciousness of the labour fishers. In terms of class conflict, there is a significant deviation from the pattern of class conflict described by Marx.  In capture fishery, intense and violent conflict more often take place not between the capitalist or owner of the means of production and labour. Instead, it often happens between the small and intermediate with the capitalist fishers. In such a conflict, there is a strong alliance between the owner of the means of production and the labour in both camps or small and intermediate, and capitalist classes. In other word, small and intermediate fishers and their labours unite, on the other hand, capitalists and their labours also unite in this conflict.Keyword: Balikpapan, class structure, class relation, common problem[How to Cite: Kinseng, R. (2013). Class Consciousness and Class Conflict in Capture Fishery in Indonesia. Journal of Rural Indonesia, 1(1), 57-66. Retrieved from http://ejournal.skpm.ipb.ac.id/index.php/ruralindonesia/article/view/37]